1312 Stabilising Preterm Infants (< 32 Weeks) in the Delivery Suite: Current Clinical Practice in the UK. (October 2012) - Singh, Y; Oddie, S
Abstract : Background: Resuscitation guideline for preterm infants has evolved over the last two decades but this still lacks standardisation and clear recommendations. Clinical practice in stabilising preterm infants in the delivery suite may vary from unit to unit. Aims and objectives: To find out the current clinical practice in the UK in stabilising the preterm infants in the delivery suite. Study Design and methods: Questionnaire based study carried out via internet tool (SurveyMonkey) followed by telephone interview from non-responders. Questionnaire completed by consultants, registrars or senior neonatal sisters (Band 6 and above). Results: 100% responses from all the 222 units providing neonatal care. 96% units (113 of 222 units) use plastic bags for thermoregulation in preterm infants although clinical practice varies from 27–32 weeks of gestation under what they use plastic bags. 56% units (123 of 222 units) provide prophylactic CPAP in preterm infants to prevent or treat RDS. Face mask with adjustable positive end expiratory pressure (PEEP) valve was the commonest (50%; 111 of 222 units) means of providing prophylactic CPAP. But for ventilated babies 70% units (154 of 222 units) provide PEEP routinely. 42% units (93 of 222 units) use start resuscitation of preterm infants in bended oxygen, 33% in air, and 17% use 100% oxygen. 64% units (143 of 222 units) use oxygen saturation monitor in the delivery suite while 28% don't use it routinely. Conclusion: Current clinical practice in stabilising preterm infants in the delivery suite varies significantly from unit to unit in the UK.